Financial Depth, Bank Competition and Economic Performance: A Cross-Country Analysis - Nomasomi, Ngonyama; Syden, Mishi; Kin, Sibanda; Palesa, Makhetha-Kosi (Journal of Reviews on Global Economics, 2020)
Financial sector development has been receiving a great amount of attention in literature over the years. The finance-growth nexus has been revisited several times with the desire to understand the link between the two as available empirical evidence often fails to explain what is observed in practice. Financial development and sophistication have, in more instances than one, failed to propel growth of economies, with the focus now leaning towards the role of the financial sector structure and competition in this relationship. Making use of cross-country data by applying robust panel data analysis techniques, an analysis of the paradox – the nexus between financial depth, competition and economic performance – was undertaken in the study. The findings have implications for both policy and future research.